Primary Papillary Serous Carcinoma of the Peritoneum - Jayakumar, NM; Sangam, PS; Grampurohit, VU; Myagery, AF (Nepal Journal of Obstetrics and Gynaecology, 2014)
Primary papillary serous carcinoma of peritoneum (PPSCP) is a rare type of primary peritoneal adenocarcinoma and is clinico-histopathologically indistinguishable from primary ovarian papillary serous carcinoma. A 70 -year- female presented with pain abdomen of 4 months duration. On examination partially mobile vague mass was present in the suprapubic region. Exploratory laparotomy revealed normal right ovary and the left ovary showed simple cyst. Nodular, firm tumour was seen arising from omentum and measured 20x13x9.3 cm. Microscopically tumour was composed of large sheets of polygonal cells having large hyperchromatic and pleomorphic nuclei and moderate amount of eosinophilic cytoplasm forming cribriform pattern and papillae. It has similar prognosis as that of ovarian malignancy. This case of extraovarian papillary serous carcinoma of peritoneum (EPSCP) is presented here for its rarity. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 60-62 DOI: http://dx.doi.org/10.3126/njog.v8i2.9774